FAO animal production and health paper N126 - T R Preston (FAO, 1995)
This manual has been completely rewritten and greatly extended. Its scope is no longer limited to crop residues and by-products, but considers also other feeds. Half of its contents is devoted to describing the essential principles which should assist the research worker in conducting useful and cost effective research.